Negative Feedback Role of Astrocytes in Shaping Excitation in Brain Cell Co-cultures - Khezerlou, Elnaz; Prajapati, Neela; DeCoster, Mark A. (Frontiers in Cellular Neuroscience, 2021)
Glial cells play an important role in maintaining neuronal homeostasis and may thus influence excitability in epileptogenesis. These cells in the brain have glutamate (Glu) transporters, which remove this neurotransmitter from the extracellular space. Lack of negative (-) feedback makes local neuronal circuits more excitable, potentially contributing to epileptogenic phenomena. In this study, the role of glial cells in providing (-) feedback is shown through different models of brain cells in culture imaged for intracellular calcium concentration ([Ca2+]i). Moreover, here we study the individual cells by putting them in categories. Neuronal networks with high and low (-) feedback were established by using anti-mitotics to deplete glial cells. Separate stimuli with very low subthreshold concentrations of Glu (250-750 nM) were added to cultures to test if the order of stimulations matter in regard to calcium dynamics outcomes. Additionally, KCl and ATP were used to stimulate glial cells. We found that for cultures high in (-) feedback, order of the stimulus was not important in predicting cellular responses and because of the complexity of networks in low (-) feedback cultures the order of stimulus matters. As an additional method for analysis, comparison of high (-) feedback cultures and pure astrocytes was also considered. Glial cells in pure astrocyte cultures tend to be larger in size than glial cells in high (-) feedback cultures. Potential effect of (-) feedback at the blood brain barrier (BBB) also has been considered for the inflammatory responses of nitric oxide (NO) production. The inflammatory and calcium signaling pathways both indicate the negative feedback role of astrocytes, poised between the BBB and structures deeper within the brain, where neuronal synapses are homeostatically maintained by glial uptake of neurotransmitters.